Artificial intelligence in assisted reproduction: the future for reproductive medicine - Hynniewta, Barry Cooper; Navas, Ferrill; Marbaniang, Kathrina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
An important turning point in the development of assisted reproductive technologies has come with the use of artificial intelligence (AI). Because optimising results is such a constant struggle, AI is being used in assisted reproduction. This review presents a concise yet comprehensive overview of AI applications in ART, including its role in computer-assisted semen analysis (CASA), oocyte and embryo evaluation, personalized stimulation protocols, and treatment outcome prediction. AI augments objectivity, enhances prediction precision, and facilitates individualized therapy through the utilization of extensive, intricate datasets. Commercial AI platforms are increasingly integrated into routine IVF workflows, particularly in embryo grading and selection, showing promising preliminary outcomes. The need for openness and fairness in AI research, development, and implementation, as well as the identification of issues and moral quandaries surrounding AI support, are underscored by the lack of legislation addressing AI in healthcare. The goal of the regulatory framework is to strike a middle ground between worldwide innovation and patient safety. Highlighting possible benefits, limits, and ethical issues, this comprehensive research evaluates the advancement of AI in assisted reproduction.